The Crown, the Queen, and the Structure of the Constitution - Newma, Warren J. (A resilient Crown: Canada's monarchy at the Platinum Jubilee, 2022)
"As the Queen marks seventy years on the throne, this engaging work examines Canada's constitutional monarchy. As Queen Elizabeth II marks her Platinum Jubilee in 2022, and following the controversial resignation of a governor general, much discussion and debate has taken place about the monarchy in Canada. This engaging work examines a broad range of topics related to Canada's constitutional monarchy, its present state, and future. Topics include Crown-Indigenous relations; the foundational place of the Crown in Canada's system of government; the Crown and the media; the Crown and Francophone Canada; the viceregal offices and the role of the administrator; royal tours; Canadian Chapels Royal; the Crown in Canada's geography--and Queen Elizabeth herself."-- Provided by publisher.